Optimizing Bothropstoxin-I-Derived Peptides: Exploring the Antibacterial Potential of p-BthW - Marinho Righetto, Gabriela; Alves Santos-Filho, Norival [UNESP]; Oliveira Catarin Nunes, Letícia [UNESP]; André, Camille; Souza, Julia Medeiros; Andricopulo, Adriano Defini; Martins Bispo, Paulo José; Cilli, Eduardo Maffud [UNESP]; Camargo, Ilana Lopes Baratella da Cunha (American Chemical Society (ACS), 2024)
Antimicrobial peptides are an emerging class of antibiotics that present a series of advantageous characteristics such as wide structural variety, broad spectrum of activity, and low propensity to select for resistance. They are found in all classes of life as defense molecules. A group of peptides derived from the protein Bothropstoxin-I has been previously studied as an alternative treatment against multi-drug-resistant bacteria. The peptide p-BthTX-I (sequence: KKYRYHLKPFCKK) and its homodimer, linked by disulfide oxidation through the residues of Cys11 and the serum degradation product [sequence: (KKYRYHLKPFC)2], were evaluated and showed similar antimicrobial activity. In this study, we synthesized an analogue of p-BthTX-I that uses the strategy of Fmoc-Lys(Fmoc)-OH in the C-terminal region for dimerization and tryptophan for all aromatic amino acids to provide better membrane interactions. This analogue, named p-BthW, displayed potent antibacterial activity at lower concentrations and maintained the same hemolytic levels as the original molecule. Our assessment revealed that p-BthW has a quick in vitro bactericidal action and prolonged post-antibiotic effect, comparable to the action of polymyxin B. The mode of action of p-BthW seems to rely not only on membrane depolarization but also on necrosis-like effects, especially in Gram-negative bacteria. Overall, the remarkable results regarding the propensity to develop resistance reaffirmed the great potential of the developed molecule.